Environmental variables influencing spatial and temporal patterns of fish spawning and recruitment - Mbatha, Fisokuhle Lungile (Marine Research (MA-RE) Institute, 2017)
ABSTRACT Spawning times and spawning intensity during the life cycles of some fish species found off South Africa and Norway were synthesized using data collected from the literature. The comparison of temporal patterns in spawning of South African fish species showed variable spawning times and intensity depending on the environmental conditions within that spawning habitat. Their spawning migration durations were suggested to be short since they inhabit a dynamic coastal upwelling ecosystem with intra-seasonal differences caused by changes in upwelling strength enhanced by south-easterly winds, nutrient-limited waters on the spawning grounds and stable thermal conditions. This contrasts with Norwegian fish species, which showed patterns of spawning times and durations that are restricted and confined to spring (February – May), probably due to strong, consistent seasonality, depending on primary production. This explains the inter-annual differences observed in their spawning periods, where strong south-westerly winds (downwelling), light intensity and salinity stratification could influence long spawning migrations. For Cape hakes, environmental variability influencing recruitment was further investigated on the west coast nursery grounds of the southern Benguela, particularly for deep-water Cape hake (Merluccius paradoxus). Biophysical characteristics of the west coast nursery grounds were assessed in relation to distribution of deep-water Cape hake juveniles (< 15 cm) using physical data (CTD, alongshore wind speed anomalies) and biological data (abundance/density of hake juveniles, recruitment estimates). Distinct spatial patterns of hake distribution were evident in relation to near-bottom environmental factors (temperature, salinity and oxygen). Nansen surveys conducted from 2003 – 2013 during summer (January – February) showed greater abundance of hake juveniles over the Orange Banks than in other nursery areas. The hake juveniles occurred in mid-shelf waters with oxygen depletion (2 – 3 mL O₂.L⁻¹) and hypoxic conditions (< 2 mL O₂.L⁻¹) and temperature ranges of 7 – 11 ⁰C. Salinity appeared to have less influence on hake juveniles' distribution. During spring surveys, hake catches were reduced on all nursery grounds except near Cape Columbine. There was a strong positive correlation between deep-water Cape hake recruitment indices and summer wind speed anomalies for the same year (Lag = 0 year) and with autumn wind speed anomalies of the previous year (Lag = 1 year). The relationship between winds and near-bottom oxygen concentrations on the Orange Banks is unclear and needs to be investigated.